Performance Evaluation Framework of a Small Scale Cloud based Application Using Log Data Analytics and Distancing Technique - Hariharan Krishna, Shoney Sebastian, Norton Stanley (Journal of Daoist Studies, 2026)
The fast growth of cloud-based applications has in-tensified the demand of effective, understandable and affordable performance monitoring mechanisms. Con-ventional monitoring systems can be based on intru-sive measurements, heavy telemetry, complicated ma-chine learning, which can give rise to privacy issues, resource consumption, or unknown error propagation. Recent research in cloud-native systems and enterprise data systems prioritizes identifying threats in real-time, responsiveness of the system, and transparency in oper-ations as the key elements of the modern digital services (Mamun and Saidur, 2021). Nevertheless, there exist no lightweight mechanisms to monitor the performance of the applications on the cloud platform at the application level to identify the initial indications of degradation before the user experience begins to decline.